Cost-effectiveness analysis of tislelizumab plus chemotherapy versus placebo plus chemotherapy as first-line treatment for advanced gastric or gastroesophageal junction adenocarcinoma: perspectives from the United States and China - Wenwang Lang; Qi Ai; Wenwen Zhang; Qinling Jiang; Yulong He; Ming Ouyang (Frontiers Media S.A., 2024)
PurposeThe efficacy of tislelizumab plus chemotherapy in improving progression-free survival (PFS) and overall survival (OS) in unresectable gastric or gastroesophageal junction cancer (GC/GEJC) has recently been emphasized. This study compared the cost-effectiveness of tislelizumab plus chemotherapy versus placebo plus chemotherapy for the United States (US) and Chinese populations.MethodsUsing data from the RATIONALE-305 phase 3 trial, a Markov model was developed to analyze quality-adjusted life years (QALYs), incremental cost-effectiveness ratios (ICERs), incremental net health benefits (INHBs), and incremental net monetary benefits (INMBs). The health state utilities and direct medical costs were obtained from the relevant literature and local cost databases. The model uncertainty was evaluated using sensitivity analyses.FindingsIn the base-case analysis, the addition of tislelizumab to chemotherapy yielded an ICER of $37,768.48 per QALY in China, slightly below the willingness-to-pay (WTP) threshold of $38,042.49 per QALY, showing marginal cost-effectiveness with an INHB of 0.05 QALYs and an INMB of $1,852.49. Subgroup analyses revealed ICERs of $23,853.52 for patients with a PD-L1 TAP score ≥ 5% (TAP ≥ 5%). In the US, the ICER was $502,786.22 per QALY in the intent-to-treat (ITT) and $321,395.28 per QALY in the TAP ≥ 5% subgroup, exceeding the US WTP threshold of $150,000.00.ImplicationsIn China, tislelizumab plus chemotherapy is a cost-effective first-line therapy for unresectable GC/GEJC in both ITT and TAP ≥ 5% subgroups. In the US, tislelizumab plus chemotherapy is not cost-effective.